Analysis of the Role of Narrative Imagination in the Civic Education of Fifth Graders in three Educational Institutions in the City of Medellin (Papeles, 2025)
Introduction: This article presents an analysis of the role of narrative imagination in the processes of civic education for fifth-grade students in three educational institutions in Medellín, Colombia. Based on the concept of narrative imagination proposed by Nussbaum, the study explores the potential of literature to foster civic skills such as empathy, critical thinking, and respect for diversity. Methodology: This research adopts a qualitative approach with a phenomenological design. Data were collected through semi-structured interviews, which were subsequently subjected to an in-depth analysis of the lived experiences and perceptions of teachers regarding the use of literature as a formative tool. Results and Discussion: The findings reveal that literature, when supported by active and intentional teacher guidance, not only enhances linguistic competencies but also fosters empathy and the recognition of otherness in students. Literary works facilitate reflection on ethical and social issues. Conclusions: Literature, from the perspective of narrative imagination, is fundamental for the integral formation of students, enabling them to reflect on their role in society and develop civic skills. This study underscores the need to strengthen teacher training in literary strategies that promote the construction of critical, ethical, and empathetic citizenship.
Keywords: Narrative imagination; civic education; cognitive and emotional development; literature; education